Clinical characteristics and outcomes of children with Kawasaki disease combined with sepsis in the pediatric intensive care unit - Yang, Yufan; Huang, Jiaotian; Yan, Haipeng; Li, Xun; Liu, Pingping; Zhou, Wu; Zhang, Xinping; Lu, Xiulan; Xiao, Zhenghui (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Kawasaki disease (KD) is a vascular inflammatory disease with unknown pathogenesis. There are few studies on KD combined with sepsis worldwide. Purpose: To provide valuable data regarding clinical characteristics and outcomes related to pediatric patients with KD combined with sepsis in pediatric intensive care unit (PICU). Methods: We retrospectively analyzed the clinical data of 44 pediatric patients admitted in PICU at Hunan Children’s Hospital with KD combined with sepsis between January 2018 and July 2021. Results: Of the 44 pediatric patients (mean age, 28.18±24.28 months), 29 were males and 15 were female. We further divided the 44 patients into two groups: KD combined with severe sepsis (n=19) and KD combined with non-severe sepsis (n=25). There were no significant between-group differences in leukocyte, C-reactive protein, and erythrocyte sedimentation rate. Interleukin-6, interleukin-2, interleukin-4 and procalcitonin in KD with severe sepsis group were significantly higher than those in KD with non-severe sepsis group. And the percentage of suppressor T lymphocyte and natural killer cell in severe sepsis group were significantly higher than those in non-severe group, while the CD4+/CD8+ T lymphocyte ratio was significantly lower in KD with severe sepsis group than in KD with non-severe sepsis group. All 44 children survived and were successfully treated after intravenous immune globulin (IVIG) combined with antibiotics. Conclusion: Children who develop with KD combined with sepsis have different degrees of inflammatory response and cellular immunosuppression, and the degree of inflammatory response and cellular immunosuppression is significantly correlated with the severity of the disease.